An Evaluation of the Readiness of Corporate Governance Frameworks to deal with Crises: A Covid-19 Perspective - Paseka Nicolas, Masiu (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.